Islamic Puritanism and Wahhabi Development - Murtado, Diran; Waehama, Muhammad Roflee (Parahyangan Catholic University, 2024)
This study explores the impact and ideology of Wahhabism within Islamic puritanism, focusing on its historical development and contemporary implications. It aims to analyze Wahhabi thought's origins, principles, and influence on Islamic revival movements and interpretations of rituals and values. Adopting a qualitative approach, data is drawn from primary sources like the Qur'an, Hadith literature, and secondary sources such as academic articles and books. Wahhabism, led by Muhammad ibn 'Abd al-Wahhab, emerged in the 18th century to purify Islam, rejecting intellectualism, mysticism, and cultural diversity, advocating for a literal interpretation of texts. This ideology has influenced modern Islamic movements and contributed to religious violence, impacting the interpretation of Islamic principles amidst contemporary dynamics. In conclusion, this research underscores Wahhabism's lasting influence on Islamic thought, shaping debates on orthodoxy, cultural identity, and political ideology within the Muslim world, contributing to a deeper understanding of Islamic puritanism's complexities and its global implications.